Biophysical modeling reveals the transcriptional regulatory mechanism of Spo0A, the master regulator in starving Bacillus subtilis - Yujia Zhang; Cristina S. D. Palma; Zhuo Chen; Brenda Zarazúa-Osorio; Masaya Fujita; Oleg A. Igoshin (mSystems)
ABSTRACT In starving Bacillus subtilis bacteria, the initiation of two survival programs—biofilm formation and sporulation—is controlled by the same phosphorylated master regulator, Spo0A~P. Its gene, spo0A, is transcribed from two promoters, Pv and Ps, that are, respectively, regulated by RNA polymerase (RNAP) holoenzymes bearing σA and σH. Notably, transcription is directly autoregulated by Spo0A~P binding sites known as 0A1, 0A2, and 0A3 box, located in between the two promoters. It remains unclear whether, at the onset of starvation, these boxes activate or repress spo0A expression, and whether the Spo0A~P transcriptional feedback plays a role in the increase in spo0A expression. Based on the experimental data of the promoter activities under systematic perturbation of the promoter architecture, we developed a biophysical model of transcriptional regulation of spo0A by Spo0A~P binding to each of the 0A boxes. The model predicts that Spo0A~P binding to its boxes does not affect the RNAP recruitment to the promoters but instead affects the transcriptional initiation rate. Moreover, the effects of Spo0A~P binding to 0A boxes are mainly repressive and saturated early at the onset of starvation. Therefore, the increase in spo0A expression is mainly driven by the increase in RNAP holoenzyme levels. Additionally, we reveal that Spo0A~P affinity to 0A boxes is strongest at 0A3 and weakest at 0A2 and that there are attractive forces between the occupied 0A boxes. Our findings, in addition to clarifying how the sporulation master regulator is controlled, offer a framework to predict regulatory outcomes of complex gene-regulatory mechanisms.IMPORTANCECell differentiation is often critical for survival. In bacteria, differentiation decisions are controlled by transcriptional master regulators under transcriptional feedback control. Therefore, understanding how master regulators are transcriptionally regulated is required to understand differentiation. However, in many cases, the underlying regulation is complex, with multiple transcription factor binding sites and multiple promoters, making it challenging to dissect the exact mechanisms. Here, we address this problem for the Bacillus subtilis master regulator Spo0A. Using a biophysical model, we quantitatively characterize the effect of individual transcription factor binding sites on each spo0A promoter. Furthermore, the model allows us to identify the specific transcription step that is affected by transcription factor binding. Such a model is promising for the quantitative study of a wide range of master regulators involved in transcriptional feedback.